How Does Corporate Social Responsibility Disclosure Affect Firm Value: Firm Maturity and Firm Financial Risk Context - Nurjanah, Intan; Arifa, Choirunnisa (The Indonesian Journal of Accounting Research, 2023)
Corporate Social Responsibility (CSR) is an activity based on altruistic reasons, but CSR disclosure also requires careful implementation consideration so that CSR disclosure becomes a tool that benefits various parties, both for different stakeholders and for the company. This study aims to examine the level of corporate maturity and corporate financial risk in moderating the relationship between CSR disclosure and firm value. The sample of this research is a non-financial company listed on the Indonesia Stock Exchange. The final sample size is 28 companies consisting of 168 observations from 2014 to 2019. The data in this study were analyzed using multiple linear regression analysis and moderated regression analysis through SPSS version 25. The results show that CSR disclosure reduces firm value in companies in Indonesia. However, the variable maturity of the company can moderate the direction of the influence of CSR on firm value from negative to positive at a significant level. Furthermore, the company's financial risk variable is also able to moderate the direction of the influence of CSR and firm value to be positive and significant. These two moderating variables are empirically important contingency factors for companies in Indonesia. This shows that the influence of CSR and corporate value is not entirely positive or negative, but is influenced by certain conditions that make CSR disclosure beneficial to all parties. This research is expected to provide an overview for company management to carry out CSR implementation through careful consideration decisions starting from planning to evaluation, to produce CSR disclosures that increase corporate value and provide value to outsiders.